Poverty Reduction and Insurance-Based Risk Protection - Aisyah Abdul Jabbar; Meguellati Achour; Edwards Geraldine; Muhammad Iqbal; Kaleem Chaghtai; Arjun Nath; Camila Garcia; Muthoifin; Ishmah Afiyah (Solo International Collaboration and Publication of Social Sciences and Humanities, 2023)
This study aims to evaluate the effectiveness of poverty reduction and insurance-based risk protection programs in a particular region, another purpose is to analyze the impact of Insurance on systematic risk protection and poverty reduction with a critical analysis approach. The method used involves a survey of a sample of program beneficiary communities as well as primary and secondary data analysis. Data were collected through interviews, observations, and documentation to identify the program's impact on poverty levels and household economic sustainability. The results showed that the program succeeded in increasing people's access to health services and education, as well as reducing financial risks faced by vulnerable households. In addition, this program also contributes positively to local economic growth and financial independence of beneficiary communities. The implications of these findings provide support for government policies to improve the effectiveness of social protection programs and expand health insurance coverage for vulnerable communities to address poverty and economic risks. The research recommends intensive education programs, stakeholder cooperation, and regulatory updates. The implications of this research highlight the need for increased public understanding, regulatory updates, and innovative product development to support the sustainable growth of Insurance.